Globalization Issued to Disruption Era: Human Resource Management Strategies of Governance Organizations - Singtho, Panjadach; Jedaman, Pornchai; Ariyasirichot, Wachirawat; Sonwa, Seksan (International Journal of Sociologies and Anthropologies Science Reviews, 2022)
Challenges to human resource management of the knowledge, skill, behavior, competence appropriate to the nature of the job, a good attitude and the relationship between personnel to operators and leaders as well as a having to job satisfaction. This study’s goal was to provide an overview of globalization issued to the disruption era on human resource management strategies of governance organizations under the new concept of government management as well as guidelines for personnel management of government organizations towards the transition to achieve value and organizational goals. In addition, the significant globalization issued to a disruption era in human resource management strategies including HR. strategic alignment, HR. operational efficiency, HRM. programmed effectiveness, HR. accountability, HRM. quality of work life. Finally, the guidelines for successful human resource management as the leaders were professional and technical knowledge, development competencies, ability to change management, and integration competencies. However, human resource management of government organizations within the evolving and ever-changing globalization era such as requires adaptation to be able to survive effectively.